2006
DOI: 10.1007/s11434-006-2164-3
|View full text |Cite
|
Sign up to set email alerts
|

A 780-year record of explosive volcanism from DT263 ice core in east Antarctica

Abstract: Ice cores recovered from polar ice sheet received and preserved sulfuric acid fallout from explosive volcanic eruptions. DT263 ice core was retrieved from an east Antarctic location. The ice core is dated using a combination of annual layer counting and volcanic time stratigraphic horizon as 780 years (1215-1996 A.D.). The ice core record demonstrates that during the period of approximately 1460-1800 A.D., the accumulation is sharply lower than the levels prior to and after this period. This period coincides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…Delmas et al [36] suggested that the deposition of volcanic ash depended strongly on the snow accumulation rate of the site, and the signals of volcanic eruption could be more significant at low accumulation rate sites. In addition, the volcanic eruptions vary remarkably in respect of the eruption materials, eruption ways, and deposition processes [4,37] . As to a Greenland ice core, about 1/3 of the volcanic events were obscured due to the local environmental conditions [33] .…”
Section: The Volcanic Events Recordmentioning
confidence: 99%
“…Delmas et al [36] suggested that the deposition of volcanic ash depended strongly on the snow accumulation rate of the site, and the signals of volcanic eruption could be more significant at low accumulation rate sites. In addition, the volcanic eruptions vary remarkably in respect of the eruption materials, eruption ways, and deposition processes [4,37] . As to a Greenland ice core, about 1/3 of the volcanic events were obscured due to the local environmental conditions [33] .…”
Section: The Volcanic Events Recordmentioning
confidence: 99%
“…Due to the extreme climatic condition at Dome A, the model results need, however, to be validated by, for instance, shallow ice cores before they can be applied reliably. So far, there are two shallow ice cores along the traverse from the Chinese Zhongshan Station to Dome A (i.e., DT001 [9,10] and DT263 [11] ) that had been studied in detail, but both cores are too shallow to penetrate the firn layer, and their time scale does not exceed 1000 a.…”
mentioning
confidence: 99%
“…We infer that this event may be the source of either the AD 1030 or AD 1257 volcanic sulphate spikes recorded in Antarctic ice sheet records (Budner and Cole-Dai 2003;Zou et al 2006) on account of their associated southern hemisphere cooling signals (Oppenheimer 2003). Based on our estimates of erupted mass and sulphur release, the caldera forming eruption cloud of Tofua would have emitted 520 ppm S per unit mass of erupted magma.…”
Section: Eruption Magnitude and Sulphur Releasementioning
confidence: 85%